2021
DOI: 10.1007/s00294-021-01155-6
|View full text |Cite
|
Sign up to set email alerts
|

Negative control of cytokinesis by stress-activated MAPK signaling

Abstract: Mitogen-activated protein kinase (MAPK) signalling pathways regulate multiple cellular functions in eukaryotic organisms in response to environmental cues, including the dynamic remodeling of the actin cytoskeleton. The fission yeast S. pombe is an optimal model to investigate the conserved regulatory mechanisms of cytokinesis, which relies in an actomyosin-based contractile ring (CAR) that prompts the physical separation of daughter cells during cellular division. Our group has recently shown that p38 MAPK or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, further evidence demonstrated that actin filaments nucleated by For3, the formin that assembles the actin cables that participate in polarized secretion and growth, also contribute to CAR formation in fission yeast [24, 25]. In turn, the activated SAPK pathway down-regulates in S. pombe CAR assembly and stability in response to stress by reducing For3 levels [25, 63]. Like animal cells, fission yeast respiratory metabolism induces endogenous oxidative stress with electron leakage from the mitochondrial electron transport chain [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, further evidence demonstrated that actin filaments nucleated by For3, the formin that assembles the actin cables that participate in polarized secretion and growth, also contribute to CAR formation in fission yeast [24, 25]. In turn, the activated SAPK pathway down-regulates in S. pombe CAR assembly and stability in response to stress by reducing For3 levels [25, 63]. Like animal cells, fission yeast respiratory metabolism induces endogenous oxidative stress with electron leakage from the mitochondrial electron transport chain [49].…”
Section: Discussionmentioning
confidence: 99%
“…[ 56 ] Sty1 is an ortholog of mammalian p38. [ 57,58 ] and the activation of the Sty1 pathway extends CLS in fission yeast. [ 59,60 ] Myriocin also extends the lifespan of nematodes, and a mutant of serine palmitoyl transferase 1 ( spt‐1 ), the target of myriocin, extends lifespan.…”
Section: Low‐molecular Weight Compounds That Extend the Chronological...mentioning
confidence: 99%
“…The stress-activated protein kinase pathway plays a critical role in S. pombe by modulating the cell cycle and the general adaptive response to stress, and its central element, the p38 ortholog mitogen-activated protein kinase (MAPK) Sty1, is activated in response to various cues including hyperosmotic stress, heat shock, cold stress, oxidative stress, and nutrient starvation (Madrid et al, 2021;Morigasaki et al, 2013;Morigasaki & Shiozaki, 2010).…”
Section: Ecl1 + Induction By Oxidative Stressmentioning
confidence: 99%
“…The stress‐activated protein kinase pathway plays a critical role in S. pombe by modulating the cell cycle and the general adaptive response to stress, and its central element, the p38 ortholog mitogen‐activated protein kinase (MAPK) Sty1, is activated in response to various cues including hyperosmotic stress, heat shock, cold stress, oxidative stress, and nutrient starvation (Madrid et al, 2021; Morigasaki et al, 2013; Morigasaki & Shiozaki, 2010). In S. pombe , oxidative stress is transmitted intracellularly through a multistep phosphorelay system consisting of the sensor kinases Mak1, Mak2, and Mak3; histidine‐containing phosphotransfer protein Mpr1; and response regulator Mcs4 (Lushchak, 2010; Papadakis & Workman, 2015; Vivancos et al, 2006).…”
Section: Signal Network Involved In Ecl Family Protein Inductionmentioning
confidence: 99%